Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1007/s10964-008-9298-3
|View full text |Cite
|
Sign up to set email alerts
|

Daily and Compulsive Internet Use and Well-Being in Adolescence: A Diathesis-Stress Model Based on Big Five Personality Traits

Abstract: This study examined the associations between adolescents' daily Internet use and low well-being (i.e., loneliness, low self-esteem, and depressive moods). We hypothesized that (a) linkages between high levels of daily Internet use and low well-being would be mediated by compulsive Internet use (CIU), and (b) that adolescents with low levels of agreeableness and emotional stability, and high levels of introversion would be more likely to develop CIU and lower well-being. Data were used from a sample of 7888 Dut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
124
2
9

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(160 citation statements)
references
References 34 publications
17
124
2
9
Order By: Relevance
“…Of the adolescents who frequently engage in online gaming, those who are more extraverted were less likely to become addicted to using the Internet. Introversion has been implicated in Internet and online gaming addiction time and again (Huang, et al, 2010;van der Aa, et al, 2009;Young, 2009). Interestingly, in this study low extraversion (or introversion) has been found to increase the risk of Internet addiction only among online gamers.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…Of the adolescents who frequently engage in online gaming, those who are more extraverted were less likely to become addicted to using the Internet. Introversion has been implicated in Internet and online gaming addiction time and again (Huang, et al, 2010;van der Aa, et al, 2009;Young, 2009). Interestingly, in this study low extraversion (or introversion) has been found to increase the risk of Internet addiction only among online gamers.…”
Section: Discussionmentioning
confidence: 47%
“…Other research has indicated that online gaming addiction may be related to neuroticism, anxiety, and sensation seeking (Mehroof & Griffiths, 2010). Apart from online gaming, research indicates that adolescent Internet addicts score significantly lower on extraversion compared to non-addicted adolescents (Huang et al, 2010), have low emotional stability, low extraversion, and low agreeableness (van der Aa et al, 2009). In summary, low emotional stability, low agreeableness, and low extraversion seem convincing candidates for increasing the risk of Internet addiction as these associations are found in multiple studies.…”
mentioning
confidence: 99%
“…Secondly, we want to address the relationship between internalizing/externalizing symptoms and FB overuse/FB addiction. Many researchers argued that neuroticism, a personality trait that characterized by anxiety, fear, moodiness, worry, envy, frustration, jealousy and loneliness, was significantly associated with SNS addiction/problematic use [49][50][51][52][53][54]. In addition, a large body of research in literature has assessed the association between depression and FB addiction.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 21 studies were identified that used miscellaneous criteria. Of these, 14 studies used miscellaneous criteria to identify Internet addiction in adolescents [40][41][42][43][44][45][46][47][48][49][50][51][52]. In addition to the adolescent samples, miscellaneous classification criteria for Internet addiction have been used in adult samples, including a total of eight studies [53][54][55][56][57][58][59][60].…”
Section: Miscellaneous Diagnostic Assessment Toolsmentioning
confidence: 99%
“…A total of 13 studies used miscellaneous criteria to identify Internet addiction in adolescents [40][41][42][43][44][45][46][47][48][49][50][51][52]. Sample sizes varied from including 1,098 adolescents in Singapore [43] to 73,238 adolescents in South Korea [51].…”
Section: Prevalence Of Internet Addiction In Adolescentsmentioning
confidence: 99%